2021
DOI: 10.1007/s10995-021-03160-0
|View full text |Cite
|
Sign up to set email alerts
|

The Time has Come for All States to Measure Racial Discrimination: A Call to Action for the Pregnancy Risk Assessment Monitoring System (PRAMS)

Abstract: Introduction Racial/ethnic inequities in preterm birth (PTB) are well documented. Most of this research has focused on maternal behavioral and socio-demographic characteristics. However, the full magnitude of the racial/ethnic gap remains inadequately understood. Studies now point to the role of racial discrimination in producing PTB inequities, but limitations exist, namely the use of a single, dichotomous item to measures discrimination and the limited generalizability of most studies which have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Additionally, most of the 48 participating PRAMS states do not include the survey item about experiences of racism, which limits the ability of researchers and practitioners to understand the prevalence and impacts of experiences of interpersonal racism in the perinatal period. We support the call for PRAMS to revise their measure of racism to be more comprehensive, use a validated measure and include the measure as a core mandatory measure in all participating state surveys (Almeida et al, 2021). The measure of depression used by PRAMS is also a limitation because it is a single item that is not diagnostically valid.…”
Section: Limitationsmentioning
confidence: 71%
“…Additionally, most of the 48 participating PRAMS states do not include the survey item about experiences of racism, which limits the ability of researchers and practitioners to understand the prevalence and impacts of experiences of interpersonal racism in the perinatal period. We support the call for PRAMS to revise their measure of racism to be more comprehensive, use a validated measure and include the measure as a core mandatory measure in all participating state surveys (Almeida et al, 2021). The measure of depression used by PRAMS is also a limitation because it is a single item that is not diagnostically valid.…”
Section: Limitationsmentioning
confidence: 71%
“… 27 More states should consider incorporating the question on socially assigned race into their PRAMS surveys. 28 In addition, due to the cross-sectional nature of the PRAMS data, we were not able to conduct a formal mediation analysis to understand the potential mediating role of thinking about race, treatment by race, or nativity status on the impact of social racial ascription on women's and infant's health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to a review of self-reported racism and health, studies with time-frame exposures that are unspecified or a year or less have significantly higher health outcomes compared to lifetime and 1 to 5-year time-frame exposures, possibly because they are the same exposures and/or because it reduces recall bias ( Paradies, 2006 ). An important focus for future research on the etiology of GDM is to improve the measure of discrimination in a way that captures the various types, as well as when and in what context it occurs ( Almeida et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%